A history of the Inquisition of the Middle Ages. Volume I - Lea, Henry Charles, 1825-1909. (Auckland : The Floating Press, 2012)
This detailed analysis of one of the most brutal periods of religious persecution ever recorded is a must-read for history buffs of all stripes. Author Henry Charles Lea lends detail and dimension to the historical record, providing a turn-by-turn recounting of events along with deeper insight into the motives and psychology of the persecutors and persecuted.
Title; Contents; Preface; BOOK I -- ORIGIN AND ORGANIZATION; Chapter I -- The Church; Chapter II -- Heresy; Chapter III -- The Cathari; Chapter IV -- The Albigensian Crusades; Chapter V -- Persecution; Chapter VI -- The Mendicant Orders; Chapter VII -- The Inquisition Founded; Chapter VIII -- Organization; Chapter IX -- The Inquisitorial Process; Chapter X -- Evidence; Chapter XI -- The Defence; Chapter XII -- The Sentence; Chapter XIII -- Confiscation; Chapter XIV -- The Stake; Appendix; Endnotes
Description based on online resource; title from PDF title page (Ebsco, viewed August 14, 2012).
Includes bibliographical references.
Keywords: Inquisition -- History; Heresy; Religion; RELIGION / Christian Church / History; RELIGION / Christianity / History; Electronic books